PENGARUH STRATEGI DISKON TERHADAP LOYALITAS PELANGGAN DI PLATFORM SHOPEE - Pio Risqi Fil’ilmi; Didi Andrianus Manalu; Intani Nur Aidah Tara; Ruvia Barnanti; Asral, Asral (Musytari : Jurnal Manajemen, Akuntansi, dan Ekonomi, 2025)
In the current digital era, the development of e-commerce in Indonesia is experiencing rapid growth, which is marked by the emergence of various online shopping platforms. This creates increasingly tight competition among e-commerce industry players, including Shopee. As one of the leading platforms, Shopee adopts a marketing strategy in the form of providing discounts to attract consumer attention and build customer loyalty. This research aims to analyze the influence of discount strategies on customer loyalty on the Shopee platform. The research method used is a quantitative approach through surveys with path analysis. The research results show that discounts have a significant positive relationship with customer loyalty (r = 0.68, p < 0.05) and contribute 46.24% to the formation of loyalty. The types of discounts most sought after by customers include direct discounts, which provide immediate price cuts, and free shipping programs, which eliminate shipping costs. Apart from that, supporting factors such as price transparency, availability of goods, and ease of the checkout process also influence the effectiveness of discount strategies. This research provides insight for Shopee to optimize discount strategies to maintain customer loyalty in the face of market competition.